Student Attendance Tool with Radio Frequency Identification Integrated Web-Based Images - Abrar, Ahmad Jawahirul; Siswono, Hartono (International Journal of Multi Discipline Science (IJ-MDS), 2024)
Attendance is a data collection activity to determine the number of students present. This also applies to the learning process at school. Collecting attendance data manually has several weaknesses, such as inaccurate data when calculating the number of student attendance. This study aimed to create tools to make data collection easier. The tool that made the writer can be explained through the main block diagram which is divided into four parts: input block, process block, output block, and wireless block. In the input block, the RFID module and Esp32cam as student identifiers. In the process block, the Esp8266 microcontroller is the main processing unit to regulate the conditions of the tool being made. The output block includes a TFT LCD screen that displays streaming video during the attendance process. The results showed that the designed device worked well when the image size on the database was the same as the frame size in Base64 format and on a TFT screen measuring 240x320. There was also RFID where a good distance for the tag card to be identified or read on the RFID reader was 0.5 cm to 2.5 cm. This system could improve accuracy and efficiency in student attendance management while providing easy access to information to all interested parties.